Cadre’s Assistance of the Integrated Health Service Post (Posyandu) Effectively Improves Adherence of Pregnant Women Taking Iron Supplements in West Sorong Health Center - Situmorang, Cory; Dewi, Ni Nyoman Sri Artina; Kinanti, Kinanti (Jurnal Bidan Cerdas, 2025)
Background: The leading cause of maternal death in Indonesia is postpartum hemorrhage resulting from uterine atony. This can be exacerbated if women experience anemia during pregnancy. Women experience anemia due to the body's lack of iron.  This study was conducted to determine the effectiveness of cadre assistance's integrated health service post using a flip sheet on the compliance of pregnant women consuming iron supplement tablets at the West Sorong Health Center. Method: This study used quasi-experimental research with a Nonequivalent Control Group Design. The study sample consisted of 34 people, divided into two groups which are control and intervention groups. Statistical tests using Wilcoxon, Mann-Whitney, and N-Gain Score. Results: the final results of adherence to taking iron supplement tablets in the experimental group showed that the majority of pregnant women had a high level of compliance, characterized by P-Value = <0.001. On the other hand, the final results of the level of compliance in the control group, the majority of respondents were at a low level of compliance characterized by P-Value = 0.058. After going through the Mann-Whitney test, the P-Value = <0.001 (P-value <0.05) shows that the alternative Hypothesis is accepted. Conclusion: The conclusion in this study was that the assistance of integrated health service post cadres was carried out for 14 days 6 times in the intervention group using the flip sheet media, influenced the compliance of pregnant women in the intervention group of taking iron supplement tablets higher than in the dick group with low compliance, the effectiveness of integrated health service post cadre assistance using flip sheets on the compliance of pregnant women taking blood supplement tablets at the West Sorong Health Center with moderate effectiveness.